SITUATION IN THE SUBJECT OF TECHNOLOGY AT PRIMARY SCHOOLS IN SLOVAKIA DURING DISTANCE EDUCATION - BANESZ, Gabriel; LUKACOVA, Danka (Trends in education, 2022)
Since 2020, the whole world has been fighting a coronavirus pandemic that continues to the present day. Education at primary schools in the Slovak Republic therefore returned to the distance form after a short break. The content of the curriculum of individual subjects at all levels of schools had to be re-adjusted so that learners acquire at least basic knowledge, skills and habits. At primary schools, there is a group of subjects which, according to the guidelines of the Ministry of Education, have become the complementary subjects, the teaching of which is not compulsory during a pandemic. Such subjects also include the subject of Technology. With its content, it focuses on acquiring the necessary knowledge and practical skills from various fields of technology. Acquiring practical manual skills in the home environment without the necessary technical support is quite problematic. For this reason, the paper presents possible ways of solving this problem, which the authors used at the selected primary school, where the subject of technology is taught even during a pandemic. These are instructional videos that have been created for pupils so that they can acquire the necessary skills at home. Instructional videos contain simple instructions for practical skills in making various projects. According to these instructional videos, the pupils proceeded and made individual assignments. Therefore, the article also presents the attitudes of pupils from personal interviews, which they presented after the implementation of individual lessons with instructional videos. The paper also presents the readiness of the addressed pupils for distance learning from the home environment.
Keywords: coronavirus pandemic; distance education; instructional videos